2014
DOI: 10.3346/jkms.2014.29.10.1372
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics for Preventing Radiation-Induced Morphological Changes in Intestinal Mucosa of Rats

Abstract: Radiation therapy is an important treatment modality for abdominal or pelvic cancer, but there is a common and serious complication such as radiation-induced enteritis. Probiotics is reported to have positive effects against radiation-induced enteropathy. In this study, morphological changes of bowel mucosa were analyzed in rats to presume the effect of probiotics on radiation-induced enteritis and its correlation with radiation dose. A total of 48 adult male Sprague-Dawley rats were randomly assigned to two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…VH was measured from the tip to the crypt-villus junction, and CD from the crypt-villus junction to the base (21) . The mucosal thickness was defined as the distance from the base of muscularis mucosa to the tip of the villus (22) .…”
Section: Histologymentioning
confidence: 99%
“…VH was measured from the tip to the crypt-villus junction, and CD from the crypt-villus junction to the base (21) . The mucosal thickness was defined as the distance from the base of muscularis mucosa to the tip of the villus (22) .…”
Section: Histologymentioning
confidence: 99%
“…The most important reason for limiting the RT dosage is that, during RT, normal tissues are exposed to radiation along with the cancerous tissues (2,3). After the bone marrow, the gastrointestinal system (GIS) is the region most sensitive to the effects of radiation because of its rapid mitotic activity and, following RT, radiation-induced enteritis and/ or colitis generally occur (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, chemical agents and oral nutritional supplements were used to reduce these complications associated with RT (1,3,7,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…39 Findings from animal studies have suggested that probiotics may prevent radiation-induced enteritis, a common and serious complication of radiation treatment for abdominal or pelvic cancer. 40 A review of 14 RCTs provided some evidence for the safe use of a strain of Lactobacillus reuteri for reducing the incidence of acute gastroenteritis in children, and preventing and treating some functional GI disorders, such as colic and regurgitation in infants. 41 Evidence for using probiotics such as L. GG and S. boulardii to prevent and treat "travelers' diarrhea" has been suggested, but is inconclusive, given the small number of clinical studies to date.…”
Section: Inflammatory Bowel Disease-a Considerable Body Of Research Lmentioning
confidence: 99%